2004
DOI: 10.1177/021849230401200108
|View full text |Cite
|
Sign up to set email alerts
|

Multivessel Total Arterial Revascularization via Left Thoracotomy

Abstract: Off-pump coronary artery bypass grafting is now becoming the preferred method of coronary revascularization. The trend is towards complete revascularization, preferably arterial. We are describing here a method of multivessel, total arterial, complete revascularization via an anterolateral thoracotomy approach in 27 patients. There was an average of 3.2 grafts/patient. Angiograms were performed in 9 patients (33.33 %). There were no operative mortalities. None of the patients required conversion to cardiopulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…30,31 In 2 other publications, single-center thoracotomy multivessel grafting with a configuration similar to that in the present series was reported in as many as 255 patients. 27,32 Although the thoracotomies were larger (allowing central cannulation via the right atrial appendage and aorta) and used external sternotomy off-pump CABG instruments through the incision, the authors noted good results, including low mortality and an incidence of atrial fibrillation that ranged between 5.5% and 8%.…”
Section: Mics Cabg Versus Other Multivessel Minimally Invasive Technisupporting
confidence: 77%
“…30,31 In 2 other publications, single-center thoracotomy multivessel grafting with a configuration similar to that in the present series was reported in as many as 255 patients. 27,32 Although the thoracotomies were larger (allowing central cannulation via the right atrial appendage and aorta) and used external sternotomy off-pump CABG instruments through the incision, the authors noted good results, including low mortality and an incidence of atrial fibrillation that ranged between 5.5% and 8%.…”
Section: Mics Cabg Versus Other Multivessel Minimally Invasive Technisupporting
confidence: 77%
“…À exceção do paciente com oclusão de enxerto, todos os demais tiveram o teste ergométrico negativo após 60 dias da operação. O crescimento das populações de maior risco, como os diabéticos [9] e os pacientes submetidos a múltiplos procedimentos [10], pode mudar a maneira como indicamos a cirurgia para a RM face ao custo adicional de reintervenções com uso das próteses farmacológicas de alto custo.…”
Section: Resultsunclassified
“…There are very few studies [1][2][3] in literature, which have reported complete primary revascularization via a thoracotomy incision . We present our initial experience using this approach to off pump coronary artery revascularization.…”
mentioning
confidence: 99%